1992
DOI: 10.1346/ccmn.1992.0400111
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Layer Charge, Charge Location, and Energy Change on Expansion Properties of Dioctahedral Smectites

Abstract: Abstract--Expansion properties of ten homoionic smectites that differed in amount and location of layer charge were examined by X-ray powder diffraction analysis at various relative humidities, or after glycerol or ethylene glycol solvations. Except for K-samples with glycerol solvation, and Na-and Ca-samples with ethylene glycol, differences in the basal spacings are observed in samples having similar layer charge. These results show that the basal spacings are larger when the layer charge is located in octah… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

31
258
0
2

Year Published

1994
1994
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 303 publications
(291 citation statements)
references
References 29 publications
31
258
0
2
Order By: Relevance
“…Atomic coordinates for the different layer types were set as recommended by Moore and Reynolds (1989), and the structural formula determined from chemical analyses was used to define the layer composition. The d 00l of the different layer types was adjusted as needed within the limits given by Sato et al (1992) to improve the quality of the fit (Table I).…”
Section: Xrd Analysesmentioning
confidence: 99%
See 1 more Smart Citation
“…Atomic coordinates for the different layer types were set as recommended by Moore and Reynolds (1989), and the structural formula determined from chemical analyses was used to define the layer composition. The d 00l of the different layer types was adjusted as needed within the limits given by Sato et al (1992) to improve the quality of the fit (Table I).…”
Section: Xrd Analysesmentioning
confidence: 99%
“…Three types of layers have been considered in the mixed layering depending on their respective layer charges (Sato et al 1992):…”
Section: Xrd Patterns Of Oriented Samples (< 1μm Fraction)mentioning
confidence: 99%
“…Sato et al, 1992) or modelled by molecular dynamic approaches (Tambach et al, 2004;Chavez-Paez et al, 2001). The number of water layers in the interlayer depends on the nature of the interlayer cations and on the compaction degree (Kozaki et al, 1998;Ferrage et al, 2005).…”
Section: Introductionmentioning
confidence: 99%
“…Both the assumptions of a constant strain broadening associated with interparticle swelling at 17 ~, (Eberl and Srodon, 1988) and of the absence of broadening induced by mixed-layering for even-order reflections of Ca-saturated (2 water-layer smectite) illitic I/S (Eberl and Blum, 1993) also seem unrealistic. Srodon (1980) and Sato et al (1992) indeed showed that the basal spacing ofa homoionic smectite (hydrated or ethylene-glycol solvated) varies significantly as a function of layer charge, charge location, relative humidity, and expansion energy.…”
Section: Fourier Analysis Of X-ray Diffraction Profile Broadeningmentioning
confidence: 95%